Analysis Of Socio-Technical Factors In Business Intelligence Framework Case Study Of Higher Learning Institution - Jayakrishnan, Mailasan (2018)
The contradictory pressures and features of socio-technical factors in an organization that relates to people, processes, and technologies, create data value on organizational strategic performance using Business Intelligence (BI) engine within different conceptual frameworks and their impact on strategy development and implementation for strategic performance management. Existing studies have not sufficiently designated the interactions between all seven (7) socio-technical factors or their influences on BI utilization. The specific features of Knowledge Management (KM) and BI in this study have been outlined as a guideline for research in viewing the big picture in decision making processes when implementing organizational performance diagnostics framework. The research goal of this study was to develop an organizational performance framework of socio-technical factors that influence on BI utilization. This study identified sociotechnical factors with observing MIT90s and McKinsey seven (7) S’s framework of people (staff, skills, and style), processes (strategy and structure) and technologies (systems and shared values) and their influences on BI utilization. The data needed for the study was collected from 474 current administration and academic staff of University A with the help of a 25-item questionnaire-based survey were developed for this research literature-based proposed model. The study utilized reliability analysis results to analyze 7 usable socio-technical factors. Data analysis was conducted with SPSS and results confirmed that shared values-oriented factors predicted knowledge seeking and contributing in BI utilization. Furthermore, reliability measurement was confirmed between 7 usable socio-technical factors including people (staff - 0.810, skills – 0.801 and style – 0.796), processes (strategy – 0.771 and structure – 0.780) and technologies (systems – 0.790 and shared values – 0.850). These findings extend the relevance and statistical power of existing studies on BI usage for displaying an organizational performance indicator.